classification results on simulated datasets and biomarkers and classification results for GAC dataset. - Fatemeh Keikha (20917848) (2025)
Each panel shows the ROC curves for four disease states in: (A) D1 with 30 genes, (B) D2 with 50 genes, and (C) D3 with 100 genes. (D) Dynamic Biomarkers for GAC. (E) ROC Curve for GAC dataset. (F) ROC curve for independent verification.